Understanding the Factors Influencing User Adoption of Fintech Lending - Nurjannah, Afifah Zahroh; Tubastuvi, Naelati; Purwidianti, Wida; Zamakhsyari, Luthfi (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
This research aims to analyze the factors that influence interest to use fintech lending among millennial communities in Central Java. This research uses the TAM (Technology Acceptance Model) theory, with independent variables namely Perceived Ease of Use, Perceived Usefulness, Relative Advantage, Perceived Risk, and Perceived Cost, the mediating variable is User Attitude and the dependent variable is Interest to Use Fintech Lending. This research is quantitative research using a purposive sampling method. The research results show that perceived usefulness and perceived risk have a positive and significant effect on user attitudes, while perceived ease of use, relative advantage, and perceived cost have no effect on user attitudes, perceived risk, and perceived cost have an effect on interest to use.